Культурне та громадсько-політичне життя міжвоєнного Луцька: національний аспект - Малеончук, Галина Олександрівна; Maleonchuk, Halyna O. (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2014)
У статті cхарактеризовано національно-культурне та громадсько-політичне життя міжвоєнного Луцька. У 1919–1939 рр. місто входило до складу Другої Речі Посполитої, що безпосередньо впливало на міжетнічні та соціальні відносини його мешканців. У цей період у Луцьку проживали євреї, поляки, українці, росіяни, німці, чехи, караїми та поодинокі представники інших народів. На основі архівних матеріалів досліджено діяльність різних політичних, економічних, культурно-освітніх, благодійних організацій. Панівну роль у політичному, громадському та культурному житті міста, попри чисельну меншість, відігравали поляки. Упродовж усього міжвоєнного періоду їх вплив посилюється. Натомість національно-культурне життя представників інших національних груп поволі згортається та підпорядковується офіційній державній політиці.

In the article author characterizes the national, cultural and sociopolitical life of the interwar Lutsk. The city was a part of the Second Polish Republic in 1919 – 1939, that directly impacts on interethnic relations and social changes of relationships of its inhabitants. In this period, Lutsk was inhabited by Jews, Poles, Ukrainians, Russians, Germans, Czechs, Karaims and solitary representatives of other nations. Based on archival materials, the author researches activities of the various political, economic, cultural, educational and charitable organizations. Poles played a dominant role in political, social and cultural life of the city, in spite of numerous minority. Throughout the interwar period, their impact is intensified. However the national and cultural life of other ethnic groups gradually have been decrising and subordinating official state policy. Keywords: Second Commonwealth, Lutsk, minorities, the national structure of the population, public organization.
Cultural and sociopolitical life of the interwar Lutsk: national aspect
Keywords: Друга Річ Посполита; econd Commonwealth; Луцьк; Lutsk; національні меншини; minorities; національна структура населення; the national structure of the population; громадська організація; public organization